Optimasi Penyeimbangan Beban Gardu Distribusi Terhadap Penurunan Rugi Energi dengan Metode Seimbang Beban Seharian - Muh. Hanif Haris; Ahmad Rizal Sultan (Elposys: Jurnal Sistem Kelistrikan, 2020)
One of the problems that often arise in distribution systems is load imbalance in meeting electric power needs. If there is a load imbalance in the 3 phase system, the neutral wire in the transformer will be energized. This will cause losses or can be said as unused energy and does not turn into rupiah. For this reason, it is necessary to balance the load of the distribution substations so that the losses that occur do not get bigger. Based on SPLN SE 17: 2014, it is said that the large percentage of load imbalance in distribution substations that can still be tolerated is below 20%, while for distribution substations with an imbalance percentage above 20%, load balancing is necessary. Based on the Transfomer Report of PT. PLN (Persero) ULP Maros, the percentage of load imbalance at the GT.MBS027 substation before load balancing is 44.783% and after load balancing there is a decrease in the percentage of imbalance to 6.867%.Likewise, the total value of energy losses before balancing is 80.802 kWh per day. After the load balancing is done, the amount of lossesdecreases to 2.95 kWh per day. So that you can save 77,852 kWh every day. If converted to a span of 30 days, it can be saved at a powerof 900 kVA of Rp. 3,157,677.12 and at a power of 1300 kVA and above it can be saved of Rp. 3,426,920.47.